ANALISIS SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS PADA PERUSAHAAN LISTRIK NEGARA (PERSERO) RAYON GIANYAR - Ni Putu Erviani Astari; Ni Komang Urip Krisna Dewi (Sekolah Tinggi Ilmu Ekonomi Wiyatamandala, 2023)
The cash receipts and disbursement accounting information system requires a good procedure or system that will later be in accordance with established management policies. The existence of an established accounting information system will facilitate performance in management and can prevent the occurrence of misappropriation of cash. This study aims to: determine whether the implementation of cash receipts and disbursement accounting information systems has fulfilled the basic elements of accounting information systems. The object ofthis research is PT PLN (PERSERO) Rayon Gianyar. The analytical method used is descriptive method and the type of research used is qualitative. Based on the research results, PT PLN has fulfilled the basic elements of an accounting information system, but some of the cash receipts and disbursements of the system are carried out centrally so as to minimize the occurrence of cash misappropriations in the company.